Investigation of the Effect of Hydrophilicity on Oxygen Reduction Reaction Property with Measurement of Water Vapor Specific Surface Area - Satoko TAKASE (The Electrochemical Society of Japan, 2021)
For oxygen reduction reaction of an air battery which uses oxygen and water as reactants, it is important to control not only gas diffusivity but also hydrophilicity. In this study, the effect of hydrophilicity was investigated quantitatively. Various hydrophilic reaction layers were prepared with different amounts of Nafion as hydrophilic binder. The hydrophilicity was evaluated by measuring water vapor adsorption and nitrogen adsorption isotherms and calculating specific surface area by Brunauer-Emmett-Teller (BET) method. Polarization curves of oxygen reduction reaction revealed that the hydrophilicity effect differs between the reaction rate-determining range and the diffusion rate-determining range. In the reaction rate-determining range, the oxygen reduction current increased in proportion to the amount of water in the reaction layer, indicating the extension of the three-phase interface as the reaction field. In the diffusion rate-determining range, oxygen reduction current decreased with increasing the hydrophilicity, which demonstrates that high hydrophilicity suppressed oxygen diffusion.